Enhancing Remote Patient Monitoring with Ai-Powered Virtual Assistants - Manpreet Kaur; Kuldeep Singh; Sukhwinder Kaur (International Journal of Bioinformatics and Computational Biology, 2026)
Artificial Intelligence (AI) is transforming personalized education by tailoring learning materials to meet the distinct needs, preferences, and progress of individual students. This paper explores how AI technologies—such as machine learning, natural language processing, and adaptive learning systems are improving the effectiveness of personalized learning experiences. Through AI, students benefit from timely feedback, access to intelligent tutoring systems, and data-driven insights that enable educators to enhance their teaching strategies. Additionally, AI-powered chatbots, recommendation systems, and automated assessments foster a more engaging and efficient educational environment. While challenges such as data privacy concerns, potential biases, and implementation costs must be addressed, the potential of AI to revolutionize education by enhancing accessibility, engagement, and learning outcomes is substantial. This study highlights key advancements, challenges, and future opportunities in the field of AI-enhanced personalized learning.
Keywords: AI-Powered Virtual Assistants; Chronic Disease Management; Remote Patient Monitoring; Telehealth; and Predictive Analytics